Des réussites bien particulières dans un dispositif de coprésence du champ de la protection de l’enfance : entre énigmes et paris - Kim Stroumza; Marc Pittet; Anne-Françoise Pont; Laetitia Krummenacher; Flavio Fersini (Recherches en Éducation)
This article focuses on moments of copresence between a parent, a child, and a professional in the course of ordinary activities (chatting, eating, playing, etc.) within a placement apparatus in the field of child protection in Switzerland. Adopting a work analysis approach, we seek to describe not only how this apparatus prompts professionals, parents, and children to act and how it acts upon them, but also how the professionals inhabit it. We look at how they engage with and disengage from the power relations inherent to a compulsory-assistance apparatus as they carry out their activities ; how, they are able to encourage effects (reciprocal implication, participation in and appropriation of the apparatus) that they may not be deliberately pursuing but that at times constitute a rather singular form of success.